Effect of feeding frequency on Nile tilapia, Oreochromis niloticus (L.) fries performance during sex reversal in hapas - Sanches, Luís Eduardo Ferrari (2008)
Research aimed at verifying the necessary feeding frequency for the best performance of Nile tilapia, Oreochromis niloticus (Perciformes, Cichlidae) fries during sex reversal period in green waters. Approximately 1,600 seven-day-old fries, measuring 9.03mm and weighting 9.77mg, in a distribution of 80 fries/hapa, were fed on diet containing 43% of CP and 60mg of methyltestosterone/kg of diet at frequencies of 2, 3, 4, 5 and 6 feedings/day, divided equally over the light period, for 28 days. Parameters of growth, survival, uniformity, feed conversion and total biomass produced were measured. Growth was significantly (p < 0.05) reduced at the frequency of 2 times per day. Regression models were used to measure the effects of feeding frequency on total biomass, and on final average weight and length. Frequency of 4-to-5 feedings/day was the most adequate. Survival, variation coefficient, uniformity condition factor, feed conversion and cost variables were not affected by the feeding regimen. The results recommend the feeding of tilapia fries at least at 4 equally spaced times during the day during the sex reversal period in order to attain best performance.